The Incidence of uro-genital fistulae at Dr George Mukhari hospital : a three-year review - Gqamlana, S. K. (University of Limpopo (Medunsa Campus), 2007)
BACKGROUND: Urogenital fistula is a gynaecological condition which arises as a consequence of an abnormal communication between the urinary system (comprising of ureters, urinary bladder and the urethra) and the vagina. The condition can be classified broadly as congenital or acquired fistula. The former is extremely rare but the latter broad category (acquired fistula); is a common gynaecological condition, which can arise as a result of obstetric, surgical, malignant and radiation causes. The aetiology of urogenital fistulae is dependent on the availability and adequacy of obstetric care, malignancy rates and types of previous pelvic surgery that a woman had undergone. The true incidence of this condition is difficult to ascertain because of the pattern of causes between the developed world and the third world. While fistulae arising from obstetric causes are the predominant ones seen in the developing world, previous surgery is known to be the main cause of 2 fistulae in most middle and high income countries. This is particularly true for many parts of the third world, where the battle against poverty and illiteracy prevent many patients from seeking medical help. Apart from vaginal birth trauma, intervention with the use of forceps/vacuum for assisted vaginal delivery and the need for surgical intervention for delivery by caesarean section, surgical procedures such as hysterectomies and radiation therapy for malignancy are other contributory aetiological factors, for urogenital fistulae. The annual worldwide incidence of urogenital fistulae is estimated to be 50,000 – 100,000 cases with the vast majority of these occurring in the developing world. The consequence of formation of fistula is the resultant urinary incontinence which the patient is subjected to. This often leads to physical and emotional pain, as the woman is rejected by her partner and family, due to the foul smelling product of incontinence. While some have advocated conservative management of this condition with a simple in-dwelling catheter, with the possibility of spontaneous resolution of the fistula, such an approach is known to alleviate the incontinence only in a small number of cases and is dependent on both the aetiological factor, the size of the fistula, as well as the area of the pelvic organ that is involved. Therefore, the 3 vast majority of the fistulae have to be resolved through surgical management. Urogenital fistulae, present a challenge to the gynaecological surgeon and if the condition is left untreated the vulval skin is at considerable risk for ammoniacal dermatitis and vulval excoriation. The occurrence and management of this condition constitutes an increasingly common urogynaecological service at Dr George Mukhari hospital (DGMH). However, despite years of dealing with this condition, there has been no systematic evaluation of this problem in this hospital. It is for this reason that this review was undertaken. OBJECTIVES: The review has focused on establishing both the incidence, the type of fistulae as well as prevailing factors that are associated with occurrence of urogenital fistulae at DGMH. The review also evaluated the success and adequacy of the surgical modalities used at DGMH. DESIGN: It was a retrospective, case-review of urogenital fistulae which were managed over a three-year period . 4 SETTING: The review was conducted at the Dr George Mukhari/MEDUNSA hospital complex – a tertiary referral center, situated approximately 32 kilometers from the city of Pretoria (South Africa). METHODOLOGY: All cases of urogenital fistulae which were managed between 1st June 2003 till 31st May 2006 (3-year review), were included in this review. The records of all patients treated during this period were retrieved for analysis. Information regarding pre-treatment assessment and diagnosis was extracted from each case file and entered into a data collection form. All the cases were managed surgically using either fistula repair, ureteric re-implantation or urinary diversion using the Wallace or Bricker’s technique. Outcome measures for this review were: demographics of the women, history of pregnancy and mode of delivery, types of previous surgical management and causes of the fistulae. Other information gleaned from the files, included past history of radiation therapy, history of treatment for pelvic inflammatory disease (PID) and any other treatment for infections. Records (both 5 short-term and long-term) were assessed for post-operative outcomes – i.e. total correction of incontinence. RESULTS: Over the three-year review period, 50 cases of urogenital fistulae were managed at DGMH and all the 50 case files were available for analysis. The ages of the patients ranged widely from 22 to 85 years. Malignant conditions (46% carcinoma of the cervix and 2% of endometrial carcinoma), constituted the majority of all the aetiological factors. This was followed by 26% obstetric causes and 26% caused by previous surgical procedures. The odds ratio for a woman presenting with fistula, having an underlying malignant factor rather than obstetric or previous surgery was 1.8 (95% confidence interval: 1.70 – 2.35). There were 84% vesico-vaginal fistulae (VVF); 14% uretero-vaginal and 2% of urethro-vaginal fistulae. Twenty-two patients (44.9%) had urinary diversion while 6 (12.2%) patients needed ureteric re-implantation and the remaining 18 cases had fistula repair. Three patients with malignancy as aetiological factor, did not undergo surgical correction because of either an underlying cardiac condition or deterioration in their health prior to the operation. Surgical outcome, revealed complete success with a single surgical 6 intervention in 42 cases (85.7%), 3 of which had a nephrostomy, prior to definitive surgical management and 4 patients needed re-laparotomy. Only two patients were reported to have been treated for wound sepsis following surgery. CONCLUSION: Contrary to what is reported in the literature, obstetric cause for urogenital fistulae was over shadowed by the predominance of malignant conditions in our institution. The high success rate achieved with surgical management of fistulae has made this condition, an easily treatable gynecological problem in our hospital
Thesis (M Med. (Obstetrics and Gynecology)) --University of Limpopo, 2007.
Keywords: Uro-genital fistulae